PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Fitri Yani Rusmawan; Mufti Nugroho (Human Capital Development, 2015)
Purpose- aiming of this research is to provide guidelines for management on how to keep staff motivated in achieving company goals. Design/methology/approach- Repondents are 50 persons the whole staffs of Restoran FJ Grill Kemang Village. In this research the descriptive analysis is applied. Findings- Motivation and work environment hyave contributed to work performance in a moderate scale. There are more variables needed to solve the problem. Research limitations- The respondents are comparatively young to provide honour responsive answer. Practical implications- There are some variable to be incuded